Core cooling and thermal responses during whole-head, facial, and dorsal immersion in 17 °C water - Pretorius, T.; Gagnon, D. D.; Giesbrecht, G. G. (Applied Physiology, Nutrition, and Metabolism, 2010)
This study isolated the effects of dorsal, facial, and whole-head immersion in 17 °C water on peripheral vasoconstriction and the rate of body core cooling. Seven male subjects were studied in thermoneutral air (~28 °C). On 3 separate days, they lay prone or supine on a bed with their heads inserted through the side of an adjustable immersion tank. Following 10 min of baseline measurements, the water level was raised such that the water immersed the dorsum, face, or whole head, with the immersion period lasting 60 min. During the first 30 min, the core (esophageal) cooling rate increased from dorsum (0.29 ± 0.2 °C/h) to face (0.47 ± 0.1 °C/h) to whole head (0.69 ± 0.2 °C/h) (p < 0.001); cooling rates were similar during the final 30 min (mean, 0.16 ± 0.1 °C/h). During the first 30 min, fingertip blood flow (laser Doppler flux as percent of baseline) decreased faster in whole-head immersion (114 ± 52%/h) than in either facial (51 ± 47%/h) or dorsal (41 ± 55%/h) immersion (p < 0.03); rates of flow decrease were similar during minutes 30 to 60 (mean, 22.5 ± 19%/h). Total head heat loss over 60 min was significantly different between whole-head (120.5 ± 13 kJ), facial (86.8 ± 17 kJ), and dorsal (46.0 ± 11 kJ) immersion (p < 0.001). The rate of core cooling, relative to head heat loss, was similar in all conditions (mean, 0.0037 ± 0.001 °C/kJ). Although the whole head elicited a higher rate of vasoconstriction, the face did not elicit more vasoconstriction than the dorsum. Rather, the progressive increase in core cooling from dorsal to facial to whole-head immersion simply correlates with increased heat loss.